Preparation method of halogen-free asphalt flame retardant

By forming a hydrotalcite-like composite flame retardant with SbO3- ion intercalation in the asphalt, the problems of toxic gas release and flame retardant segregation during asphalt pavement combustion are solved, achieving a highly efficient and stable flame retardant effect.

CN120005283BActive Publication Date: 2025-11-25SUZHOU ZHONGTIAN ROAD TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510224189.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-11-25
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

Existing asphalt pavements release toxic gases when burned in tunnels, and flame retardants are prone to segregation in asphalt, resulting in unstable flame retardant effects.

Method used

Al(OH)3, Mg(OH)2 and Sb2O3 are used to form a hydrothermal reaction with SbO3- ion intercalation in the interlayer. This is then coated on the surface of expandable graphite to form a composite flame retardant. The composite flame retardant is then ground to a particle size of less than 2μm using a nano-sand mill and reacted in an autoclave.

Benefits of technology

It improves the synergistic effect of flame retardants, reduces the risk of segregation, enhances flame retardant efficiency and performance stability, and the preparation process generates no waste.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120005283B_ABST
    Figure CN120005283B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of asphalt flame retardant preparation, and particularly relates to a halogen-free asphalt flame retardant preparation method. The specific step process of the halogen-free asphalt flame retardant preparation method is as follows: slurry preparation: taking Al(OH)3 90-110 g, Mg(OH)2 280-320 g, and Sb2O3 90-110 g; pretreatment: performing surface modification treatment on Al(OH)3 and Mg(OH)2, removing impurities in Sb2O3, and ensuring the purity; the flame retardant Mg(OH)2, Al(OH)3 and Sb2O3 are subjected to high-temperature and high-pressure hydrothermal reaction to realize atomic-level mixing of Mg, Al and Sb elements, form interlayer SbO3 ‑ The ion intercalated hydrotalcite-like substance is attached to the surface of the expandable graphite to form a composite flame retardant. The components of the composite flame retardant have strong synergistic effect, the risk of segregation of the flame retardant is greatly reduced, the flame retardant efficiency is high, the performance is stable, and there is no three waste emissions in the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of asphalt flame retardant preparation, in particular to a halogen-free asphalt flame retardant preparation method. BACKGROUND

[0002] With the development of highway construction in China, the number and scale of highway tunnels also increase year by year. Higher requirements are put forward for the safety and comfort of the tunnel pavement, and cement concrete has been difficult to meet the requirements of modern tunnel pavement. Compared with cement concrete, asphalt concrete pavement has high flatness, good skid resistance, low noise and less dust. Asphalt concrete pavement has become the mainstream of current tunnel pavement. However, while meeting the comfort requirements, asphalt pavement also brings new problems. Asphalt is an organic matter, which releases a large amount of smoke and toxic gases when burning. In a relatively closed tunnel or tunnel, once a fire occurs, the toxic gases released by the burning of asphalt will pose a serious threat to personal safety, and the fire will cause the temperature in the tunnel to rise, the visibility to be poor, and the rescue to be difficult, which is easy to cause subsequent accidents such as explosion. Therefore, improving the flame retardant performance of tunnel pavement asphalt has become a key problem for long and large tunnel pavement asphalt pavement.

[0003] To achieve the purpose of asphalt flame retardation, mainly through adding flame retardant to asphalt. At present, the commonly used flame-retardant and smoke-suppressing agents are: halogen, phosphorus-nitrogen, aluminum-magnesium, antimony, boron, etc. Among them, halogen combustion will produce harmful gases, phosphorus-nitrogen system has low flame-retardant effect on asphalt, magnesium-aluminum system is safe and environmentally friendly but has low flame-retardant efficiency. In order to achieve the ideal flame-retardant effect, the flame retardant needs to be compounded in most cases, and the synergistic effect between the flame retardants is used to achieve the purpose of flame retardation. However, the viscosity of asphalt is relatively low at high temperature, and different flame retardants are easy to separate in asphalt due to density difference, which reduces the synergistic efficiency and makes the flame-retardant effect unstable.

[0004] Therefore, the present application provides a halogen-free asphalt flame retardant preparation method to solve the above problems. SUMMARY

[0005] The present application aims to provide a halogen-free asphalt flame retardant preparation method to solve the problems in the background art.

[0006] To achieve the above purpose, the present application provides the following technical scheme: a halogen-free asphalt flame retardant preparation method, the specific step process of which is as follows:

[0007] Step one, slurry preparation: take Al(OH)3 90-110g, Mg(OH)2 280-320g, Sb2O3 90-110g;

[0008] Step 2, Pretreatment: Surface modification treatment is performed on Al(OH)3 and Mg(OH)2 to remove impurities inside Sb2O3 and ensure its purity;

[0009] Step 3: Mixing and dispersing: Add the above three raw materials to a container, add water and mix and stir continuously until a slurry is prepared. The stirring time should be controlled at 10-20 minutes to make the solid content of the slurry 15%.

[0010] Step 4, Slurry Grinding: Grind the slurry using a nano-grind mill until the particle size (D50) of the solid material in the slurry is less than 2μm;

[0011] Step 5, hydrothermal reaction: Transfer the ground slurry to a high-pressure reactor with a stirrer, add expandable graphite, the amount of expandable graphite added is 17-50% of the original solid matter mass of the slurry, and react for 2-12 hours under stirring at a temperature of 180-220℃. After the reaction is completed, cool to below 100℃, add 1% of dimethyl phosphate solid matter, and stir to cool down to below 60℃.

[0012] Step 6, Drying and Pulverizing: Filter the slurry, dry it, and pulverize it to obtain the composite flame retardant.

[0013] Preferably, the specific steps of the Al(OH)3 surface modification treatment in step two are as follows: aluminum hydroxide powder is gradually added to the pre-prepared silane solution while stirring rapidly to ensure that each particle can fully contact the silane coupling agent. Stirring is continued for 20-30 minutes to allow the silane coupling agent to be uniformly adsorbed on the Al(OH)3 surface and chemically bonded to it. The mixture is filtered or centrifuged to remove excess silane solution, resulting in surface-modified Al(OH)3 solid. It is then air-dried in a well-ventilated environment or placed in an oven for low-temperature drying.

[0014] Preferably, the specific steps of the Mg(OH)2 surface modification treatment in step two are as follows: spray the silane coupling agent onto the dry Mg(OH)2 powder, and use a high-speed stirrer or vibrating screen to mix the two thoroughly.

[0015] Preferably, the Al(OH)3 is of industrial grade, with an alumina content higher than 63.5% and a particle size (D50) < 5 μm.

[0016] Preferably, the Mg(OH)2 is of industrial grade, with a magnesium hydroxide content higher than 91% and a particle size (D50) < 5 μm.

[0017] Preferably, the Sb2O3 is industrial grade, and the Sb2O3 content is higher than 90%.

[0018] Preferably, the expandable graphite has a particle size of 80 mesh and an expansion ratio of 300 times.

[0019] Compared with the prior art, the beneficial effects of the present invention are:

[0020] This application achieves atomic-level mixing of Mg, Al, and Sb elements through a high-temperature, high-pressure hydrothermal reaction with flame retardants Mg(OH)2 and Al(OH)3, forming SbO3-containing interlayers. - Ion-intercalated hydrotalcite-like material is attached to the surface of expandable graphite to form a composite flame retardant. The components of this composite flame retardant have a strong synergistic effect, which greatly reduces the risk of segregation of the flame retardant. It has high flame retardant efficiency, stable performance, and no waste emissions during the preparation process. Attached Figure Description

[0021] Figure 1 This is a flowchart of the preparation steps. Detailed Implementation

[0022] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0023] In the description of this invention, it should be understood that the terms "upper", "lower", "front", "rear", "left", "right", "top", "bottom", "inner", "outer", etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this invention.

[0024] Please see Figure 1 The present invention provides a technical solution:

[0025] A method for preparing a halogen-free asphalt flame retardant, the specific steps of which are as follows:

[0026] Step 1, Slurry preparation: Weigh out 90-110g of Al(OH)3, 280-320g of Mg(OH)2, and 90-110g of Sb2O3;

[0027] Step 2, Pretreatment: Surface modification treatment is performed on Al(OH)3 and Mg(OH)2 to remove impurities inside Sb2O3 and ensure its purity;

[0028] Step 3: Mixing and dispersing: Add the above three raw materials to a container, add water and mix and stir continuously until a slurry is prepared. The stirring time should be controlled at 10-20 minutes to make the solid content of the slurry 15%.

[0029] Step 4, Slurry Grinding: Grind the slurry using a nano-grind mill until the particle size (D50) of the solid material in the slurry is less than 2μm;

[0030] Step 5, hydrothermal reaction: Transfer the ground slurry to a high-pressure reactor with a stirrer, add expandable graphite, the amount of expandable graphite added is 17-50% of the original solid matter mass of the slurry, and react for 2-12 hours under stirring at a temperature of 180-220℃. After the reaction is completed, cool to below 100℃, add 1% of dimethyl phosphate solid matter, and stir to cool down to below 60℃.

[0031] Step 6, Drying and Pulverizing: Filter the slurry, dry it, and pulverize it to obtain the composite flame retardant.

[0032] This flame retardant consists of a hydrotalcite-like compound containing magnesium, aluminum, and antimony coated on the surface of expandable graphite. The hydrotalcite-like compound contains 12.8-26% Mg, 5-11.3% aluminum, and 7-20% antimony. Mg, Al, and Sb form a layered hydrotalcite-like structure, with Mg and Al located in the layers, and Sb as SbO3. - It exists in the interlayer form, partly as an interlayer anion, and the mass ratio of hydrotalcite-like compound to expandable graphite is 6-2:1.

[0033] The specific steps of the Al(OH)3 surface modification treatment in step two are as follows: gradually add aluminum hydroxide powder to the pre-prepared silane solution while stirring rapidly to ensure that each particle can fully contact the silane coupling agent. Continue stirring for 20-30 minutes to allow the silane coupling agent to be uniformly adsorbed on the Al(OH)3 surface and chemically bonded to it. Filter or centrifuge the mixture to remove excess silane solution and obtain surface-modified Al(OH)3 solid. Air dry naturally in a well-ventilated environment or dry in an oven at low temperature.

[0034] The specific steps of the Mg(OH)2 surface modification treatment in step two are as follows: spray the silane coupling agent onto the dry Mg(OH)2 powder, and use a high-speed stirrer or vibrating screen to mix the two thoroughly.

[0035] The Al(OH)3 is of industrial grade, with an alumina content higher than 63.5% and a particle size (D50) < 5 μm.

[0036] The Mg(OH)2 is of industrial grade, with a magnesium hydroxide content higher than 91% and a particle size (D50) < 5 μm.

[0037] The Sb2O3 is industrial grade, with an Sb2O3 content higher than 90%.

[0038] The expandable graphite has a particle size of 80 mesh and an expansion ratio of 300 times.

[0039] Example 1:

[0040] The specific steps of the preparation method for this halogen-free asphalt flame retardant are as follows:

[0041] Step 1, Slurry preparation: Weigh out 90g of Al(OH)3, 280g of Mg(OH)2, and 90g of Sb2O3;

[0042] Step 2, Pretreatment: Surface modification treatment is performed on Al(OH)3 and Mg(OH)2 to remove impurities inside Sb2O3 and ensure its purity;

[0043] Step 3: Mixing and dispersing: Add the above three raw materials to a container, add water and mix and stir continuously until a slurry is prepared. The stirring time should be controlled at 10 minutes to make the solid content of the slurry 15%.

[0044] Step 4, Slurry Grinding: Grind the slurry using a nano-grind mill until the particle size (D50) of the solid material in the slurry is less than 2μm;

[0045] Step 5, hydrothermal reaction: Transfer the ground slurry to a high-pressure reactor with a stirrer, add expandable graphite, the amount of expandable graphite added is 17-50% of the original solid matter mass of the slurry, react for 2 hours under stirring at a temperature of 180℃, after the reaction is completed, cool to below 100℃, add 1% solid matter of dimethyl phosphate, stir and cool down to below 60℃;

[0046] Step 6, Drying and Pulverizing: Filter the slurry, dry it, and pulverize it to obtain the composite flame retardant;

[0047] Example 2:

[0048] The specific steps of the preparation method for this halogen-free asphalt flame retardant are as follows:

[0049] Step 1, Slurry preparation: Weigh 100g of Al(OH)3, 300g of Mg(OH)2, and 100g of Sb2O3;

[0050] Step 2, Pretreatment: Surface modification treatment is performed on Al(OH)3 and Mg(OH)2 to remove impurities inside Sb2O3 and ensure its purity;

[0051] Step 3: Mixing and dispersing: Add the above three raw materials to a container, add water and mix and stir continuously until a slurry is prepared. The stirring time is controlled at 15 minutes, so that the solid content of the slurry is 15%.

[0052] Step 4, Slurry Grinding: Grind the slurry using a nano-grind mill until the particle size (D50) of the solid material in the slurry is less than 2μm;

[0053] Step 5, hydrothermal reaction: Transfer the ground slurry to a high-pressure reactor with a stirrer, add expandable graphite, the amount of expandable graphite added is 17-50% of the original solid matter mass of the slurry, react at 200℃ for 7 hours under stirring. After the reaction is completed, cool to below 100℃, add 1% solid matter of dimethyl phosphate, stir and cool down to below 60℃.

[0054] Step 6, Drying and Pulverizing: Filter the slurry, dry it, and pulverize it to obtain the composite flame retardant;

[0055] Example 3:

[0056] The specific steps of the preparation method for this halogen-free asphalt flame retardant are as follows:

[0057] Step 1, Slurry preparation: Weigh 110g of Al(OH)3, 320g of Mg(OH)2, and 110g of Sb2O3;

[0058] Step 2, Pretreatment: Surface modification treatment is performed on Al(OH)3 and Mg(OH)2 to remove impurities inside Sb2O3 and ensure its purity;

[0059] Step 3: Mixing and dispersing: Add the above three raw materials to a container, add water and mix and stir continuously until a slurry is prepared. The stirring time should be controlled at 20 minutes to make the solid content of the slurry 15%.

[0060] Step 4, Slurry Grinding: Grind the slurry using a nano-grind mill until the particle size (D50) of the solid material in the slurry is less than 2μm;

[0061] Step 5, hydrothermal reaction: Transfer the ground slurry to a high-pressure reactor with a stirrer, add expandable graphite, the amount of expandable graphite added is 17-50% of the original solid matter mass of the slurry, react for 12 hours under stirring at a temperature of 220℃, after the reaction is completed, cool to below 100℃, add 1% solid matter of dimethyl phosphate, stir and cool down to below 60℃;

[0062] Step 6, Drying and Pulverizing: Filter the slurry, dry it, and pulverize it to obtain the composite flame retardant;

[0063] Comparative Example 1:

[0064] Weigh out 100g of Al(OH)3, 150g of Mg(OH)2, 37.5g of Sb2O3, and 48.9g of expandable graphite (accounting for 17% of the mass of the other three flame retardants), mix them evenly, and obtain comparative flame retardant 1;

[0065] Comparative Example 2:

[0066] Weigh out 100g of Al(OH)3, 200g of Mg(OH)2, 70g of Sb2O3, and 129.5g of expandable graphite (accounting for 35% of the mass of the other three flame retardants), mix them evenly, and obtain comparative flame retardant 2.

[0067] SBS modified asphalt was heated to 160℃, and 15% of different flame retardants were added to the SBS modified asphalt. The mixture was sheared for 15 minutes and stirred for 20 minutes using an emulsifier to prepare flame-retardant asphalt. Flame-retardant asphalt samples were prepared, and their smoke density and oxygen index were tested. The flame-retardant asphalt was then allowed to stand, and the oxygen index of the upper and lower layers of asphalt was tested separately. The results are shown in the table below.

[0068] Item Units Flame retardant 1 Flame retardant 2 Flame retardant 3 Comparison 1 Comparison 2 Modified bitumen Oxygen index % 26.5 27.2 26.8 24.6 25.3 19.3 Smoke density 73 71 72 83 79 88 Oxygen index difference % 0.4 0.3 0.3 1.5 1.7 0.2

[0069] As shown in the table above, the flame retardant provided by this invention has a high oxygen index, low smoke density, and strong anti-segregation ability when added to asphalt, and has good market application prospects.

[0070] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or basic characteristics. Therefore, the embodiments should be considered exemplary and non-limiting in all respects. The scope of the invention is defined by the appended claims rather than the foregoing description. Therefore, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention, and no reference numerals in the claims should be construed as limiting the scope of the claims.

[0071] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a halogen-free asphalt flame retardant, characterized in that, The specific steps of the preparation method for this halogen-free asphalt flame retardant are as follows: Step 1, Slurry preparation: Weigh out 90-110g of Al(OH)3, 280-320g of Mg(OH)2, and 90-110g of Sb2O3; Step 2, Pretreatment: Surface modification treatment is performed on Al(OH)3 and Mg(OH)2 to remove impurities inside Sb2O3 and ensure its purity; Step 3: Mixing and dispersing: Add the above three raw materials to a container, add water and mix and stir continuously until a slurry is prepared. The stirring time should be controlled at 10-20 minutes to make the solid content of the slurry 15%. Step 4, Slurry Grinding: Grind the slurry using a nano-grind mill until the particle size D50 of the solid material in the slurry is less than 2μm; Step 5, hydrothermal reaction: Transfer the ground slurry to a high-pressure reactor with a stirrer, add expandable graphite, the amount of expandable graphite added is 17-50% of the original solid matter mass of the slurry, and react for 2-12 hours under stirring at a temperature of 180-220℃. After the reaction is completed, cool to below 100℃, add 1% of dimethyl phosphate solid matter, and stir to cool down to below 60℃. Step 6, Drying and Pulverizing: Filter the slurry, dry it, and pulverize it to obtain the composite flame retardant.

2. The method for preparing a halogen-free asphalt flame retardant according to claim 1, characterized in that: The specific steps of the Al(OH)3 surface modification treatment in step two are as follows: gradually add aluminum hydroxide powder to the pre-prepared silane solution while stirring rapidly to ensure that each particle can fully contact the silane coupling agent. Continue stirring for 20-30 minutes to allow the silane coupling agent to be uniformly adsorbed on the Al(OH)3 surface and chemically bonded to it. Filter or centrifuge the mixture to remove excess silane solution and obtain surface-modified Al(OH)3 solid. Air dry naturally in a well-ventilated environment or dry in an oven at low temperature.

3. The method for preparing a halogen-free asphalt flame retardant according to claim 1, characterized in that: The specific steps of the Mg(OH)2 surface modification treatment in step two are as follows: spray the silane coupling agent onto the dry Mg(OH)2 powder, and use a high-speed stirrer or vibrating screen to mix the two thoroughly.

4. The method for preparing a halogen-free asphalt flame retardant according to claim 1, characterized in that: The Al(OH)3 is of industrial grade, with an alumina content higher than 63.5% and a particle size D50 < 5 μm.

5. The method for preparing a halogen-free asphalt flame retardant according to claim 1, characterized in that: The Mg(OH)2 is of industrial grade, with a magnesium hydroxide content higher than 91% and a particle size D50 < 5 μm.

6. The method for preparing a halogen-free asphalt flame retardant according to claim 1, characterized in that: The Sb2O3 is industrial grade, with an Sb2O3 content higher than 90%.

7. The method for preparing a halogen-free asphalt flame retardant according to claim 1, characterized in that: The expandable graphite has a particle size of 80 mesh and an expansion ratio of 300 times.

Citation Information

Patent Citations

  • Preparation method of surface-modified hydrotalcite

    CN103241752A

  • An halogen free frame retardant insulation composition

    KR1020020029178A